Rocket Stove sebagai Teknologi Alternatif Pengurangan Polusi Asap di Desa Badak Anom - Ikhsan, Muhammad Nur; Aditya, Muhammad Arif; sunaryo, Rico Aris; Baginda, Yosua Valentino; Hartanto, Aristya; Yuliani, Rina; Suta, Taqi Arya; Zulkarnaen, Haris Firdick; Hassan, Muhammad; Purnamasari, Endah (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Open waste burning remains a significant environmental issue in Badak Anom Village, contributing to air pollution that adversely affects community health. This community service program aims to introduce the rocket stove as an alternative technology for more efficient and low-emission waste management. The implementation method includes literature review, coordination and permit acquisition from local authorities, site surveys, preparation of technical drawings, construction of the rocket stove, and community training on its use. The results show that the rocket stove effectively reduces smoke emissions compared with open burning, improves combustion efficiency, and decreases the volume of organic waste by more than 70 percent. The community also demonstrated increased understanding of waste segregation and safe combustion practices. Overall, the rocket stove has proven to be an effective appropriate technology that supports sustainable waste management in rural areas.